Investigation of Daily Glucose Profile of Inpatients in Non-endocrinology Departments in Chinese Population - Sun, Xiaoyang; Gui, Minghui; Huang, Huiqun; Zhao, Huihua; Yan, Hongmei; Bian, Hua; Gao, Xin (Frontiers in Public Health, 2020)
Background: Inpatient hyperglycemia is associated with poor prognosis and increased hospitalization expenses. China has a large population of inpatients with hyperglycemia, but their glucose monitoring states (including preprandial, postprandial and bedtime glucose) are unknown, especially in non-endocrinology departments. Methods: In this cross-sectional study, 5790 patients with hyperglycemia from 31 non-endocrinology departments were enrolled, and a total of 122032 point-of-care blood glucose (POC-BG) records were collected. The “patient-day” unit of measure was used as a metric for the inpatient glucose. A total of 2763 patients from endocrinology wards were included for the comparison of the improvement of glycemic management during hospitalization in non-endocrinology wards. Results: A total of 61.16% of patient-days had <4 POC-BG tests. Postprandial POC-BG was tested significantly less frequently than preprandial POC-BG (10.60% vs. 58.85% of all records, P < 0.001). The patient-day-weighted mean BG was higher in non-ICU wards than in the ICU (9.72±3.37 vs. 9.00±3.19 mmol/L, P < 0.001). The rate of hyperglycemia (BG > 10 mmol/L) was 37.60% in all non-endocrinology wards (ICU vs. non-ICU: 33.19% vs. 39.17%, P < 0.001). In non-ICU wards, the rate of hyperglycemia (BG > 10 mmol/L) was significantly higher in surgical wards than in medical wards (40.30% vs. 36.90%, P < 0.001). ICU had a significantly higher rate of achieving the blood glucose target than the non-ICU wards (32.50% vs. 26.38%, P < 0.001). In the non-ICU departments, medical wards had higher rate of achieving the blood glucose target than surgical wards (39.70% vs. 19.08%, P < 0.001). With increasing days of hospitalization, there was no improvement in glycemic control in non-endocrinology wards. The ICU had a significantly higher rate of hypoglycemia than non-ICU wards (4.62% vs. 3.73%, P < 0.05). In non-ICU wards, medical wards had a significantly higher rate of hypoglycemia than surgical wards (5.71% vs. 2.75%, P < 0.05). Conclusions: Both the frequency of BG monitoring and the daily glucose profile of inpatients in Chinese non-endocrinology departments were less than ideal and need to be urgently improved.